Glutathione S-transferase M1 and T1 null polymorphisms and risk of oral submucous fibrosis: a meta-analysis of South Asian populations - Paria Motahari; Negin Neshanifard (BMC Oral Health)
Abstract Background Oral submucous fibrosis (OSMF) is a precancerous condition prevalent in individuals who habitually consume areca nut products. While environmental risk factors play a significant role in OSMF, genetic predisposition—particularly involving glutathione S-transferase (GST) gene deletions—may influence susceptibility. This meta-analysis aimed to evaluate the association between GSTM1-null and GSTT1-null genotypes and the risk of OSMF. Methods Relevant databases were systematically searched up to April 2025. Two reviewers independently extracted data, and analyses were performed using Meta Analyst software. Forest plots presented pooled odds ratios (OR) with 95% confidence intervals (CI). Heterogeneity, sensitivity, and publication bias were assessed using funnel plots and Egger’s tests. Results Twelve studies involving 4484 participants (1925 cases, 2559 controls) were included. The GSTM1-null genotype significantly increased OSMF risk (OR = 1.46, 95% CI: 1.08–1.97), as did the GSTT1-null genotype (OR = 1.97, 95% CI: 1.08–3.60). Sensitivity analyses confirmed robust findings, and publication bias was minimal. Subgroup analyses revealed that larger sample sizes and higher areca nut exposure amplified the observed associations. Conclusions This meta-analysis underscores the role of GST polymorphisms in OSMF pathogenesis, highlighting their potential in risk stratification and early detection strategies. Future research should explore gene-environment interactions and include multi-ethnic cohorts to generalize findings. Trial registration CRD42024628773.